Peeta Mellark in The Hunger Games : A Feminist View of “Men Written By Women” - Zhahrin, Mazaya Elsa (CV. Tripe Konsultan, 2025)
The term “men written by women” which is a new terminology on the social media platforms namely Tiktok, has sparked conversations revolving on what masculinity is. Peeta Mellark from Suzanne Collins’ The Hunger Games trilogy becomes the embodiment of the